Pengaruh Word Of Mouth, Kualitas Pelayanan, Media Sosial, Store Atmosphere, Fasilitas, Dan Harga Terhadap Loyalitas Pelanggan Pada Warkop Kidol Lepen Tulungagung - Aris Munandar; Rendra Erdkhadifa (Faculty of Islamic Economic and Business (FEBI), Sayyid Ali Rahmatullah State Islamic University (UIN SATU) Tulungagung, 2023)
The purpose of this study is to identify how word-of-mouth, service quality, social media, store atmosphere, facilities, and prices affect customer loyalty. This research uses primary data obtained from questionnaire responses distributed to customers of Warkop Kidol Lepen, Sumbergempol District, Tulungagung Regency. Warkop Kidol Lepen customers who have purchased at least 2 times as part of this research population. This research uses the Accidental Sampling type of the Non-Probability Sampling method. The sample used was 96 respondents. Validity and reliability tests, multicollinearity tests, coefficient of determination tests, stealth tests (f), partial tests (t), and classic assumption tests such as normality, autocorrelation, and heteroscedasticity tests are used to obtain and analyze data. The findings show that the variables of service quality, store atmosphere, facilities, and price have an impact on customer loyalty, whereas word of mouth and social media do not affect customer loyalty.